The potential of Data-Driven Virtual Assistants to enhance Customer Experience in the Telecommunications Industry (Human Factors in Design, 2018)
Our day to day is becoming increasingly technological. We use more devices, manage more aspects of our life online, check whatsapp dozens of times a day, etc. We have even started talking to our phones in search of information and answers to make our lives easier. This is why we keep hearing words like Virtual Assistants or Artificial intelligence, which have become familiar through Siri, Cortana or Google Assistant. We do not hesitate to ask them for information about the weather, routes, reminders, etc. However, when it comes to interacting with organisations and service providers, users still tend to do so through traditional channels, such as phone calls or visiting shops, which quite often result in a poor customer experience and low customer satisfaction. This usually happens because it has become difficult for both customers and firms to access and filter information in this overwhelming era of Data Growth, the core challenge of Big Data. Consequently, how could large organisations implement new technologies to improve customer experience and utilise Big Data? This paper explores the benefits and needs of applying Data-Driven Virtual Assistants and Artificial Intelligence principles to enhance customer experience when managing Telecommunications services, as well as what such applications would imply compared to existing models. It identifies the perceived benefits from both users and the Telecoms organisations that implement a Data Driven Virtual Assistant.